Relationship between Spiritual Experiences and Organizational Commitment with Perceived Stress at the staff of Tehran Oil Hospital - Yavari, Mohammad Reza; Zarrini, Soraya (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: There have been numerous researches carried out in the field of organizational health with the aim of identifying ways to counteract the negative effects of stress. The purpose of this study was to determine the relationship between spiritual experiences and organizational commitment with the perceived stress of the staff of the Tehran Oil Hospital. Methods: The research population of all Tehran Nursing Hospital nursing staff was stratified randomly based on the formula for determining the sample population in 2017. For data collection, standardized questionnaires were used to measure each variable and the extracted data were analyzed using SPSS 22 software. Results: Statistical analysis of the research data showed that there was a significant relationship between spiritual experiences and its components such as meaningful work, sense of correlation and alignment of values, and the pillars of the organizational commitment such as emotional commitment, continuous commitment and normative commitment with perceived stress at a significant level of P<0.05. According to the results of regression with multivariate correlation coefficient for linear combination of variables of spiritual experiences (work with meaning, sense of correlation and values alignment), organizational commitment and perceived stress were equal to MR =35.70and RS =0.19,Which is significant at P<0.0001. Conclusions: The results of this study showed that the spiritual experiences of employees have a positive and significant relationship with organizational commitment and reducing perceived stress. In other words, those with high spirituality feel less stress and more organizational commitment.